Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.4727
|View full text |Cite
|
Sign up to set email alerts
|

OP0284 Muc5b promoter variant rs35705950 is a risk factor for rheumatoid arthritis – interstitial lung disease

Abstract: BackgroundRheumatoid arthritis–associated interstitial lung disease (RA-ILD) and idiopathic pulmonary fibrosis (IPF) share phenotypic similarities. The gain-of-function MUC5B promoter variant rs35705950 is the strongest risk factor for development of IPFObjectivesWe hypothesised that rs35705950 would also contribute to the risk of ILD in RA patients.MethodsUsing a French discovery population and multi-ethnic validation populations from 6 different countries, we tested the association of the MUC5B promoter vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The cohort demographics and a description of the clinical conditions for all genotyped MVP participants and COVID-19 positive MVP participants (18) that were evaluated in this study are shown in Table 1. (22), rheumatoid arthritis with interstitial lung disease (RA-ILD) (23) and idiopathic pulmonary fibrosis (IPF)diagnosis (24). These variables were derived from the data within two years prior to the index date of diagnosis (Table E1).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The cohort demographics and a description of the clinical conditions for all genotyped MVP participants and COVID-19 positive MVP participants (18) that were evaluated in this study are shown in Table 1. (22), rheumatoid arthritis with interstitial lung disease (RA-ILD) (23) and idiopathic pulmonary fibrosis (IPF)diagnosis (24). These variables were derived from the data within two years prior to the index date of diagnosis (Table E1).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Gene variants (rare and common sequence variants in 7 genes [MUC5B, TERT, TERC, RTEL1, PARN, SFTPC, and SFTPA2; [3][4][5][6][7][8][9][10][11] ] and in at least 12 novel loci 12,13 ), environmental exposures (asbestos and microorganisms), and immune conditions (rheumatoid arthritis and scleroderma; 14 ) place individuals at risk of developing the radiographic and pathological features of UIP. The more common risk factors, such as age, male sex, cigarette smoking, and the MUC5B promoter variant predispose individuals to develop phenocopies of IPF 3 , including rheumatoid arthritis associated interstitial lung disease (RA-ILD) 15 and chronic hypersensitivity pneumonitis 16 . The heterogeneity of IPF is highlighted further by the multiple emerging epigenetic 17 and transcriptional [18][19][20] profiles reported in this disease.…”
mentioning
confidence: 99%
“…In IIP, there is a type of ILD, respiratory bronchiolitis-associated ILD, which is associated with small airway inflammation (25). Moreover, recent studies found MUC5B promoter variant in patients with RA-UIP and IPF, but not in patients with RA without ILD (26). MUC5B is a mucin secreted by bronco-epithelial cells, hence a connection between AD and ILD in RA-ILD might be suggested.…”
Section: Discussionmentioning
confidence: 99%